Optimal Management of Complicated Infections in the Pediatric Patient: The Role and Utility of Ceftazidime/Avibactam - Bassetti, Matteo (Infect Drug Resist, 2020)
Antimicrobial resistance poses a substantial threat to global public health. The pursuit of new antibiotics has decreased and very few options have been investigated for the treatment of complicated multidrug-resistant Gram-negative (MDR-GN) infections in adult population and even less in pediatric patients. Ceftazidime-avibactam (CAZ-AVI) is novel cephalosporin/β-lactamase inhibitor (BL-BLI) combination with broad antibacterial spectrum. The aim of this review is to describe the current and future role CAZ-AVI in the pediatric population with suspected or confirmed MDR-GN infections.